2011
DOI: 10.1111/j.1365-2788.2011.01497.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inclusion on the academic achievement and adaptive behaviour of children with intellectual disabilities

Abstract: Inclusive education is an appropriate educational option for primary pupils with ID who require extensive support in school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(102 citation statements)
references
References 33 publications
2
87
0
11
Order By: Relevance
“…Laws, Byrne and Buckley (2000) found that on the other hand children with ID in general education classrooms achieved significantly higher scores in vocabulary and grammar comprehension as well as a greater percentage in developed reading skills. More recently, Dessemontet, Bless and Morin (2012) found that included children with ID made slightly more progress in literacy skills than children attending special schools. No differences were found between the progress of the two groups in mathematics or adaptive behavior.…”
Section: Academic Outcomesmentioning
confidence: 99%
“…Laws, Byrne and Buckley (2000) found that on the other hand children with ID in general education classrooms achieved significantly higher scores in vocabulary and grammar comprehension as well as a greater percentage in developed reading skills. More recently, Dessemontet, Bless and Morin (2012) found that included children with ID made slightly more progress in literacy skills than children attending special schools. No differences were found between the progress of the two groups in mathematics or adaptive behavior.…”
Section: Academic Outcomesmentioning
confidence: 99%
“…Due to academic difficulties and underachievement, students with disabilities receive varying levels of special education services. However, inclusive education has been associated with improved academic outcomes for students with disabilities (Dessemontet et al 2012;Kurth and Mastergeorge 2010). In fact, Westling and Fox (2009) found that students with disabilities, taught in general education classes, tended to perform better on measures of achievement, including reading and mathematics, than students taught in partial or complete pull-out programs.…”
Section: School Technology and Extracurricular Activitiesmentioning
confidence: 99%
“…A method for developing adaptations that facilitates common language between 6 general and special educators, which includes considering the student's learning goals and IEP accommodations, individualizing teaching methods, and individualizing personal supports, has been articulated based on master-teacher input; however, this process has not been field tested (Janney & Snell, 2006). Finally, students receiving special education services often demonstrate academic underachievement (Massetti et al, 2008), and inclusive education has been associated with improved academic outcomes for students with disabilities (Dessemontet, Bless, & Morin, 2012;Kurth & Mastergeorge, 2010). Yet for inclusion to be successful, the use of adaptations is necessary to meet individual student needs (Cross, Traub, Hutter-Pishgahi, & Shelton, 2004).…”
Section: Effectiveness Of Adaptationsmentioning
confidence: 99%